Study of Tetanus in the Infectious Diseases Hospital, Dhaka, Bangladesh - Tauhid, Syed Ahsan; Siddika, Syeda Subrina; Anwer, Sk Serjina (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Background: Tetanus is a vaccine preventable serious disease that can affect people of all age group with a high mortality. Although tetanus incidence is significantly reduced due to nationwide vaccination coverage, it is not uncommon in our country. Aims & Objectives: To determine of the socio-demographic profile, nature of injury, incubation period and outcome of the tetanus patients who were admitted in the Infectious Diseases Hospital, Dhaka during the study period. Materials and Methods: This cross sectional observational study was done in the Infectious diseases hospital, Dhaka during the period of February 2017 to January 2018. The data, were collected, compiled and analyzed. Results: Out of 149 patients, neonates were 13(8.7%) in number. Most of the cases were in middle aged group. Malefemale ratio about 4.5:1. Majority of the patients (134, 89.9%) had no history of immunization but one patient was immunized within five years. Mean incubation period tetanus was 8.45 days with ±5.56 SD. Death occurs in 41(27.5%) patients and all of them had no history of immunization. Death rate of patients having early incubation period was significantly higher (p=0.003). Death rate in neonatal tetanus (53.84%) also significantly higher than that of non-neonatal tetanus (25%) (p= 0.026). Conclusion: Tetanus is not uncommon in Bangladesh, especially in neonates and adult male and mortality rate is high. Short incubation period predicts were outcome. J Bangladesh Coll Phys Surg 2021; 39(3): 160-166